ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU KAYU PADA UD RAHMA - ZAIN, VITRIA (Fakultas Ekonomi Universitas Tadulako, 2020)
Research this purpose find out optimal amount raw material puchases each time making and order, knowing the safety stok raw materials that must be provided and knowing when to re-order raw materials. This type of research is quantitative descriptif research, using the EOQ method of economical raw material purchase in 2017 is 63,67 m3. With the order frequency of 9,14 time and the optimum cycle time of each order is 31,1 days. The number of safety suppies that must be povided is 7.113,6 m3. The right time to re-order is when the raw material supply is 7.121,08 m3.